2006
DOI: 10.1126/science.1124891
|View full text |Cite
|
Sign up to set email alerts
|

Phylogeny of the Ants: Diversification in the Age of Angiosperms

Abstract: We present a large-scale molecular phylogeny of the ants (Hymenoptera: Formicidae), based on 4.5 kilobases of sequence data from six gene regions extracted from 139 of the 288 described extant genera, representing 19 of the 20 subfamilies. All but two subfamilies are recovered as monophyletic. Divergence time estimates calibrated by minimum age constraints from 43 fossils indicate that most of the subfamilies representing extant ants arose much earlier than previously proposed but only began to diversify durin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

57
802
6
33

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 723 publications
(898 citation statements)
references
References 20 publications
57
802
6
33
Order By: Relevance
“…In order to evaluate whether different approaches give Figure 1 Ant species used in this study. The divergence estimates are in My and based on large-scale sequence data from Brady et al (2006) and Moreau et al (2006). CSP evolution in ants J Kulmuni et al similar results, we made a neighbour-joining tree of each alignment and confirmed that different alignment methods produced similar overall topology.…”
Section: Sequence Alignment and Analysissupporting
confidence: 50%
“…In order to evaluate whether different approaches give Figure 1 Ant species used in this study. The divergence estimates are in My and based on large-scale sequence data from Brady et al (2006) and Moreau et al (2006). CSP evolution in ants J Kulmuni et al similar results, we made a neighbour-joining tree of each alignment and confirmed that different alignment methods produced similar overall topology.…”
Section: Sequence Alignment and Analysissupporting
confidence: 50%
“…The phylogenetic relationships given are slightly different than in figure 1. Nevertheless, using the phylogenetic relationships of Moreau et al (2006) does not qualitatively change any of our conclusions.…”
Section: Note Added In Proofmentioning
confidence: 57%
“…Recently, Moreau et al (2006) have constructed a detailed molecular phylogeny of ants. The phylogenetic relationships given are slightly different than in figure 1.…”
Section: Note Added In Proofmentioning
confidence: 99%
“…The most recent common ancestor (MRCA) of Pseudomyrmecinae dates to 71.7 + 7 Ma, significantly older than found in chronograms that focused on all ants and therefore included only a few Pseudomyrmecinae [52,53]. The stem age of Pseudomyrmex is 49.0 + 4 Ma, its crown age 35.8 + 4 Ma (figure 2; electronic supplementary material, figure S4).…”
Section: (B) Times Of Origin Of Pseudomyrmecinae and Their Plant Hostsmentioning
confidence: 99%